2022
DOI: 10.3389/fneur.2022.1030747
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms of acupuncture in enhancing cerebral perfusion of ischemic stroke

Abstract: Ischemic stroke is the predominant cause of long-term disability and death worldwide. It is attributable to the sudden interruption of regional cerebral blood flow, resulting in brain cell death and neurological impairment. Acupuncture is a widely used adjuvant treatment for ischemic stroke in China and shows promising efficacy in clinical practice. This review mainly focused on the evidence to illustrate several possible mechanisms of acupuncture therapy on cerebral perfusion in ischemic stroke. Studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…It was recommended to the world in 1979 by the World Health Organization that 43 indications of acupuncture be used, including those related to neuromuscular conditions, and acupuncture was approved for clinical use during stroke rehabilitation by the National Institutes of Health in 1997 (Liu, 2022 ). Study has shown that acupuncture has a positive effect on the recovery of cerebral perfusion, reducing degree of neurological damage, and improving prognosis for neurological function after stroke, which may related to the fact that acupuncture promotes blood vessel regeneration through the regulation of hemodynamics and the release of vasoactive substances (Wang et al, 2022 ). Moreover, acupuncture therapy promotes synaptic plasticity and facilitates nerve repair through different ways (Qing et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was recommended to the world in 1979 by the World Health Organization that 43 indications of acupuncture be used, including those related to neuromuscular conditions, and acupuncture was approved for clinical use during stroke rehabilitation by the National Institutes of Health in 1997 (Liu, 2022 ). Study has shown that acupuncture has a positive effect on the recovery of cerebral perfusion, reducing degree of neurological damage, and improving prognosis for neurological function after stroke, which may related to the fact that acupuncture promotes blood vessel regeneration through the regulation of hemodynamics and the release of vasoactive substances (Wang et al, 2022 ). Moreover, acupuncture therapy promotes synaptic plasticity and facilitates nerve repair through different ways (Qing et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture reduces whole blood viscosity, plasma viscosity, hematocrit, and profibrin levels in ischemic stroke patients. 5 In addition, acupuncture therapy improves microcirculation in ischemic areas by modulating cell metabolism-related enzymes. 54,55 Acupuncture can also modulate ischemic perfusion by targeting the endothelial nitric oxide system and the brain renin-angiotensin system.…”
Section: Ischemic Strokementioning
confidence: 99%
“…Investigating microcirculation and hemorheology is crucial for comprehensively understanding the circulatory system at the micro-level, deepening our knowledge of organ function and pathology, analyzing disease progression, predicting prognosis, and enhancing clinical efficacy. 4 Hemorheological disturbances can lead to microcirculatory disorders, which in turn can cause various diseases, such as ischemic stroke, 5 female infertility, 6 pain syndrome, 7 and so on. Microcirculatory dysfunctions play a substantial role in the prevalence, fatality rates, and health care expenses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact mechanism of action of acupuncture in post-stroke dysfunction remains unclear. Acupuncture may enhance cerebral perfusion after IS, promote hemodynamic changes, release vasoactive substances, stimulate the production of new blood vessels, and improve microcirculation [34] . Another study indicated that interventions with appropriate electrodes for IS could exert neuroprotective and neuroregenerative effects [35] .…”
Section: Introductionmentioning
confidence: 99%